Effect of sex and final fattening on ultrasound and carcass traits in Iberian pigs. - Ayuso, D; González, a; Hernández, F; Peña, F; Izquierdo, M (Meat science, 2014)
A hundred and twenty-five castrated Iberian pigs (61 males and 64 females, from 106.9 kg of live weight at star to 160.3 kg at slaughter) was used to investigate the effect of feeding system on carcass attributes (backfat thickness and loin area measured with ultrasound before slaughter, and intramuscular fat and weights and yields of hams, forelegs and loins after slaughter). Pigs were fattened outdoor under extensive conditions. There were 4 treatments: "montanera", M; "recebo", R; "cebo a campo", C; and high oleic fed, O). Ultrasound images were collected at two rib locations (10th and 14th). M and O groups had the highest fat thickness and loin area was lower in M than in C group. M and O showed higher carcass weight and yield than the other groups. The largest ham weight was for C and the lowest for M groups. Loin weight and yield were higher in M and R than the other two groups (O and C).
Keywords: Adipose Tissue; Adipose Tissue: chemistry; Adipose Tissue: ultrasonography; Animal Feed; Animal Feed: analysis; Animals; Body Weight; fatty acids; Fatty Acids: analysis; Female; Image Processing, Computer-Assisted; Male; meat; Meat: analysis; Muscle, Skeletal; Muscle, Skeletal: chemistry; Muscle, Skeletal: ultrasonography; Phenotype; Sex Factors; Swine

Effect of the pig rearing system on the final volatile profile of Iberian dry-cured ham as detected by PTR-ToF-MS - Sánchez del Pulgar, J; Soukoulis, C; Carrapiso, A I; Cappellin, L; Granitto, P; Aprea, E; Romano, A; Gasperi, F; Biasioli, F (Meat Science, 2013)
The volatile compound proﬁle of dry-cured Iberian ham lean and subcutaneous fat from pigs fattened outdoors on acorn and pasture (Montanera) or on high-oleic concentrated feed (Campo) was investigated by proton transfer reaction time-of-ﬂight mass spectrometry. In addition to the usual proton transfer ionization the novel switchable reagent ions system was implemented which allows the use of different precursor ions (H3O+ , NO+ and O2 + ). The analysis of the lean and subcutaneous fat volatile compounds allowed a good sample discrimination according to the diet. Differences were evident for several classes of compounds: in particular, Montanera hams showed higher concentrations of aldehydes and ketones and lower concentrations of sulfur-containing compounds compared to Campo hams. The use of NO+ as precursor ion conﬁrmed the results obtained with H3O+ in terms of classiﬁcation capability and provides additional analytical insights.
Keywords: aldehydes; Aldehydes: analysis; Animal Feed; Animal Husbandry; Animal Husbandry: methods; Animals; diet; Dietary Fats; Dietary Fats: analysis; Dietary Fats: pharmacology; Dry cured ham; Ions; Ketones; Ketones: analysis; Mass spectrometry; Mass Spectrometry: methods; meat; Meat: analysis; Nuts; Oleic Acid; Oleic Acid: pharmacology; Poaceae; Proton transfer reaction mass spectrometry; Quercus; Rearing system; subcutaneous fat; Subcutaneous Fat: metabolism; Sulfur Compounds; Sulfur Compounds: analysis; Swine; Switchable reagent ions; Time of flight; Volatile Organic Compounds; Volatile Organic Compounds: analysis

Rapid characterization of dry cured ham produced following different PDOs by proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS). - Del Pulgar, José Sánchez; Soukoulis, Christos; Biasioli, Franco; Cappellin, Luca; García, Carmen; Gasperi, Flavia; Granitto, Pablo; Märk, Tilmann D.; Piasentier, Edi; Schuhfried, Erna (Talanta, 2011)
In the present study, the recently developed proton transfer reaction time of flight mass spectrometry (PTR-ToF-MS) technique was used for the rapid characterization of dry cured hams produced according to 4 of the most important Protected Designations of Origin (PDOs): an Iberian one (Dehesa de Extremadura) and three Italian ones (Prosciutto di San Daniele, Prosciutto di Parma and Prosciutto Toscano). In total, the headspace composition and respective concentration for nine Spanish and 37 Italian dry cured ham samples were analyzed by direct injection without any pre-treatment or pre-concentration. Firstly, we show that the rapid PTR-ToF-MS fingerprinting in conjunction with chemometrics (Principal Components Analysis) indicates a good separation of the dry cured ham samples according to their production process and that it is possible to set up, using data mining methods, classification models with a high success rate in cross validation. Secondly, we exploited the higher mass resolution of the new PTR-ToF-MS, as compared with standard quadrupole based versions, for the identification of the exact sum formula of the mass spectrometric peaks providing analytical information on the observed differences. The work indicates that PTR-ToF-MS can be used as a rapid method for the identification of differences among dry cured hams produced following the indications of different PDOs and that it provides information on some of the major volatile compounds and their link with the implemented manufacturing practices such as rearing system, salting and curing process, manufacturing practices that seem to strongly affect the final volatile organic profile and thus the perceived quality of dry cured ham.
The following values have no corresponding Zotero field: accession-num: 21645714
Keywords: Animals; Data Mining; Dry cured ham; Flavour compounds; Food Handling; Food Handling: methods; Italy; Mass spectrometry; Mass Spectrometry: methods; Meat Products; Meat Products: analysis; PDO; PTR-MS; PTR-ToF-MS; Spain; Swine; volatile compounds; Volatile Organic Compounds

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I.; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)The following values have no corresponding Zotero field: publisher: American Chemical Society accession-num: 17990850
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco a (Journal of Agricultural and Food Chemistry, 2007)
Ellagitannin-containing foods (strawberries, walnuts, pomegranate, raspberries, oak-aged wine, etc.) have attracted attention due to their cancer chemopreventive, cardioprotective, and antioxidant effects. Ellagitannins (ETs) are not absorbed as such but are metabolized by the intestinal flora to yield urolithins (hydroxydibenzopyran-6-one derivatives). In this study, Iberian pig is used as a model to clarify human ET metabolism. Pigs were fed either cereal fodder or acorns, a rich source of ETs. Plasma, urine, bile, lumen and intestinal tissues (jejunum and colon), feces, liver, kidney, heart, brain, lung, muscle, and subcutaneous fat tissue were analyzed. The results demonstrate that acorn ETs release ellagic acid (EA) in the jejunum, then the intestinal flora metabolizes EA sequentially to yield tetrahydroxy- (urolithin D), trihydroxy- (urolithin C), dihydroxy- (urolithin A), and monohydroxy- (urolithin B) dibenzopyran-6-one metabolites, which were absorbed preferentially when their lipophilicity increased. Thirty-one ET-derived metabolites were detected, including 25 urolithin and 6 EA derivatives. Twenty-six extensively conjugated metabolites were detected in bile, glucuronides and methyl glucuronides of EA and particularly urolithin A, C, and D derivatives, confirming a very active enterohepatic circulation. Urolithins A and B as well as dimethyl-EA-glucuronide were detected in peripheral plasma. The presence of EA metabolites in bile and in urine and its absence in intestinal tissues suggested its absorption in the stomach. Urolithin A was the only metabolite detected in feces and together with its glucuronide was the most abundant metabolite in urine. No metabolites accumulated in any organ analyzed. The whole metabolism of ETs is shown for the first time, confirming previous studies in humans and explaining the long persistency of urolithin metabolites in the body mediated by an active enterohepatic circulation.
From Duplicate 2 (Iberian Pig as a Model To Clarify Obscure Points in the Bioavailability and Metabolism of Ellagitannins in Humans - Espín, Juan Carlos; González-Barrio, Rocío; Cerdá, Begoña; López-Bote, Clemente; Rey, Ana I; Tomás-Barberán, Francisco A)
Keywords: Animal; Animals; bile; bioavailability; Biological Availability; Body Fluids; Body Fluids: chemistry; Cereals; Cereals: chemistry; colon; diet; ellagic acid; Ellagitannin; gall bladder; Humans; Hydrolyzable Tannins; Hydrolyzable Tannins: metabolism; Hydrolyzable Tannins: pharmacokinetics; intestine; metabolism; Models; Quercus; Seeds; Seeds: chemistry; Swine; Swine: metabolism; Tissue Distribution; urolithin

Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro; Olivares, Álvaro (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)
Keywords: a and g tocopherols; Adipose Tissue; Adipose Tissue: metabolism; Age Factors; alpha-Tocopherol; alpha-Tocopherol: analysis; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Body Composition; Body Composition: physiology; carcass quality; fatty acid proﬁle; fatty acids; Fatty Acids: analysis; free-range fattening; gamma-Tocopherol; gamma-Tocopherol: analysis; Growth; Male; Muscle; Pig age; Skeletal; Skeletal: anatomy & histology; Skeletal: chemistry; Swine; Swine: growth & development; Weight Gain

Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro; Olivares, Álvaro (Archives of Animal Nutrition, 2006)
Abstract This experiment was carried out to study the influence of age at the beginning of the free-range fattening period (traditional pigs, TP, age 12 months vs. young pigs, YP, age 8 months) on the performance of Iberian pigs. During 152 days prior to the fattening period, TP and YP pigs received 1.7 and 2.6 kg feed per day, respectively. During fattening, TP pigs had a higher average daily gain (p < 0.05) than YP pigs. The proportions of PUFA and n-3 fatty acids of the outer and inner layers of subcutaneous backfat were higher in TP than in YP pigs (p < 0.05), while the proportions of C16:0 and SFA in the inner layer of subcutaneous backfat were greater in YP than in TP pigs (p < 0.05). The ratio of n-6/n-3 in subcutaneous backfat was lower in TP than in YP pigs (p < 0.05). The percentage of intramuscular fat in longissimus dorsi muscle was higher in TP than in YP pigs (p < 0.05). The relationship between the percentage of intramuscular fat in longissimus dorsi muscle and average daily gain during the free-range fattening period adjusted to a quadratic function (p < 0.05). The concentration of α- and ?-tocopherol in subcutaneous backfat at slaughter was significantly higher in TP than in YP pigs (p < 0.05). It is concluded that Iberian pigs that have 8 months of age at the beginning of free-range feeding have adequate commercial quality.
From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)From Duplicate 2 (Effect of age at the beginning of the free-range fattening period on growth and carcass and fat quality in Iberian pigs - Daza, Argimiro; López-Bote, Clemente; Rey, Ana; Olivares, Álvaro)The following values have no corresponding Zotero field: publisher: Taylor & Francis accession-num: 16921928
Keywords: a and g tocopherols; Adipose Tissue; Adipose Tissue: metabolism; Age Factors; alpha-Tocopherol; alpha-Tocopherol: analysis; Animal Feed; Animal Nutritional Physiological Phenomena; Animals; Body Composition; Body Composition: physiology; carcass quality; fatty acid proﬁle; fatty acids; Fatty Acids: analysis; free-range fattening; gamma-Tocopherol; gamma-Tocopherol: analysis; Growth; Male; Muscle; Pig age; Skeletal; Skeletal: anatomy & histology; Skeletal: chemistry; Swine; Swine: growth & development; Weight Gain